Polygenic Profile of Elite Strength Athletes - Moreland, Ethan; Borisov, Oleg V; Semenova, Ekaterina A; Larin, Andrey K; Andryushchenko, Oleg N; Andryushchenko, Liliya B; Generozov, Edward V; Williams, Alun G; Ahmetov, Ildus I (Journal of strength and conditioning research, 2022)
Moreland, E, Borisov, OV, Semenova, EA, Larin, AK, Andryushchenko, ON, Andryushchenko, LB, Generozov, EV, Williams, AG, and Ahmetov, II. Polygenic profile of elite strength athletes. J Strength Cond Res 36(9): 2509-2514, 2022-Strength is a heritable trait with unknown polygenic nature. So far, more than 200 DNA polymorphisms associated with strength/power phenotypes have been identified majorly involving nonathletic populations. The aim of the present study was to investigate individually and in combination the association of 217 DNA polymorphisms previously identified as markers for strength/power phenotypes with elite strength athlete status. A case-control study involved 83 Russian professional strength athletes (53 weightlifters, 30 powerlifters), 209 Russian and 503 European controls. Genotyping was conducted using micro-array analysis. Twenty-eight DNA polymorphisms (located near or in ABHD17C , ACTG1 , ADCY3 , ADPGK , ANGPT2 , ARPP21 , BCDIN3D , CRTAC1 , DHODH , GBE1 , IGF1 , IL6 , ITPR1 , KIF1B , LRPPRC , MMS22L , MTHFR , NPIPB6 , PHACTR1 , PLEKHB1 , PPARG , PPARGC1A , R3HDM1 , RASGRF1 , RMC1 , SLC39A8 , TFAP2D , ZKSCAN5 genes) were identified to have an association with strength athlete status. Next, to assess the combined impact of all 28 DNA polymorphisms, all athletes were classified according to the number of "strength" alleles they possessed. All highly elite strength athletes were carriers of at least 22 (up to 34) "strength" alleles, whereas 27.8% of Russian controls had less than 22 "strength" alleles ( p < 0.0001). The proportion of subjects with a high (≥26) number of "strength" alleles was significantly greater in highly elite strength athletes (84.8%) compared with less successful strength athletes (64.9%; odd ratio [OR] = 3.0, p = 0.042), Russian (26.3%; OR = 15.6, p < 0.0001) or European (37.8%; OR = 6.4, p < 0.0001) controls. This is the first study to demonstrate that the likelihood of becoming an elite strength athlete depends on the carriage of a high number of strength-related alleles.ABSTRACTMoreland, E, Borisov, OV, Semenova, EA, Larin, AK, Andryushchenko, ON, Andryushchenko, LB, Generozov, EV, Williams, AG, and Ahmetov, II. Polygenic profile of elite strength athletes. J Strength Cond Res 36(9): 2509-2514, 2022-Strength is a heritable trait with unknown polygenic nature. So far, more than 200 DNA polymorphisms associated with strength/power phenotypes have been identified majorly involving nonathletic populations. The aim of the present study was to investigate individually and in combination the association of 217 DNA polymorphisms previously identified as markers for strength/power phenotypes with elite strength athlete status. A case-control study involved 83 Russian professional strength athletes (53 weightlifters, 30 powerlifters), 209 Russian and 503 European controls. Genotyping was conducted using micro-array analysis. Twenty-eight DNA polymorphisms (located near or in ABHD17C , ACTG1 , ADCY3 , ADPGK , ANGPT2 , ARPP21 , BCDIN3D , CRTAC1 , DHODH , GBE1 , IGF1 , IL6 , ITPR1 , KIF1B , LRPPRC , MMS22L , MTHFR , NPIPB6 , PHACTR1 , PLEKHB1 , PPARG , PPARGC1A , R3HDM1 , RASGRF1 , RMC1 , SLC39A8 , TFAP2D , ZKSCAN5 genes) were identified to have an association with strength athlete status. Next, to assess the combined impact of all 28 DNA polymorphisms, all athletes were classified according to the number of "strength" alleles they possessed. All highly elite strength athletes were carriers of at least 22 (up to 34) "strength" alleles, whereas 27.8% of Russian controls had less than 22 "strength" alleles ( p < 0.0001). The proportion of subjects with a high (≥26) number of "strength" alleles was significantly greater in highly elite strength athletes (84.8%) compared with less successful strength athletes (64.9%; odd ratio [OR] = 3.0, p = 0.042), Russian (26.3%; OR = 15.6, p < 0.0001) or European (37.8%; OR = 6.4, p < 0.0001) controls. This is the first study to demonstrate that the likelihood of becoming an elite strength athlete depends on the carriage of a high number of strength-related alleles.